Gender Differences within the Firm: Evidence from Two Million Travelers - Javier D. Donna; Gregory F. Veramendi (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We document gender differences in the price paid for work-related air travel among similar workers within a firm. We show that women pay consistently less per ticket than men, after accounting for a large set of covariates that include the characteristics of the trips, the employers, and the employees. A large proportion of the lower fares paid by women is explained by women booking flights earlier than men. We investigate potential mechanisms that could explain the observed gender differences. We find that gender differences increase with age, but we find no deviation from this trend during the childbearing years. We also find significant variation in gender differences across the regions of the world. Using country-level data on preference differences, we report that positive and negative reciprocity are factors associated with the documented gender differences, although this result is only suggestive. The documented gender differences have important monetary implications for firms and suggest a potentially important role for workers' morale within a firm.
Keywords: D91; J16; F00; L93; M50; 330; gender differences; worker gender differences; airline industry